2016
DOI: 10.3386/w22863
|View full text |Cite
|
Sign up to set email alerts
|

Is it the "How" or the "When" that Matters in Fiscal Adjustments?

Abstract: Using data from 16 OECD countries from 1981 to 2014 we study the effects on output of fiscal adjustments as a function of the composition of the adjustment-that is, whether the adjustment is mostly based on spending cuts or on tax hikes-and of the state of the business cycle when the adjustment is implemented. We find that both the "how" and the "when" matter, but the heterogeneity related to the composition is more robust across different specifications. Adjustments based upon permanent spending cuts are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 2 publications
2
39
0
Order By: Relevance
“…Note. The table reports the cumulated and cumulated as fraction of cumulated primary surplus multipliers obtained from the Transition AutoRegressive (STAR) model with two states, recession and expansion, and a nonlinearity associated with the composition of a …scal plan (Alesina et al (2017a). 90 percent bootstrapped (1000 repetitions) con…dence intervals for the …rst column and one standard deviation for the second in parentheses.…”
Section: Resultsmentioning
confidence: 99%
“…Note. The table reports the cumulated and cumulated as fraction of cumulated primary surplus multipliers obtained from the Transition AutoRegressive (STAR) model with two states, recession and expansion, and a nonlinearity associated with the composition of a …scal plan (Alesina et al (2017a). 90 percent bootstrapped (1000 repetitions) con…dence intervals for the …rst column and one standard deviation for the second in parentheses.…”
Section: Resultsmentioning
confidence: 99%
“…This implicitly assumes that the estimated fiscal multiplier for discretionary spending is similar for other revenue and spending components, including discretionary changes in the tax system and automatic stabilisers. Existing studies typically show that the impact of these other components on aggregate demand tends to be somewhat weaker than that of discretionary fiscal spending (Alesina et al, 2016;Ramey, 2016). Consequently, the simulations in this section may somewhat overstate the impact on unemployment of changes in the headline and cyclically-adjusted fiscal balance.…”
mentioning
confidence: 93%
“… The monetary policy response. Fiscal multipliers are larger when monetary policy does not respond to the demand stimulus by raising interest rates, which is typically the case at the zero interest lower bound (Alesina et al, 2016;Woodford, 2011).…”
mentioning
confidence: 99%
“…On this last point, Afonso and Jalles (2012); Alesina and Ardagna (1998); Alesina and Perotti (1995); McDermott and Wescott (1996), among others, found that successful fiscal consolidations mainly rely on expenditure cuts rather than tax increases, and e.g. Alesina and Ardagna (2013); Alesina et al (2015Alesina et al ( , 2018; Heylen et al (2013); Schaltegger and Feld (2009) conclude that fiscal consolidations led by spending cuts are more likely to generate growth and reduce deficits/debt than those led by tax hikes.…”
Section: Introductionmentioning
confidence: 99%